2013
DOI: 10.1242/jeb.081331
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of environmental light alters reception and production of visual signals in Nile tilapia

Abstract: SUMMARYSignal reception and production form the basis of animal visual communication, and are largely constrained by environmental light. However, the role of environmental light in producing variation in either signal reception or production has not been fully investigated. To chart the effect of environmental light on visual sensitivity and body colouration throughout ontogeny, we measured spectral sensitivity, lens transmission and body pattern reflectance from juvenile and adult Nile tilapia held under two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 62 publications
6
32
0
Order By: Relevance
“…This agrees with developmental plasticity demonstrated in other fishes such as the black bream (Shand et al 2008). The only study to examine adult plasticity showed that adult tilapia were not plastic to altered lighting environments (Hornsby et al 2013). This lack of adult plasticity is similar to studies of the South American species Aequidens pulcher, which found no shifts in photoreceptor sensitivities when fish were reared under different colored lights in the lab (Wagner and Kroger 2005).…”
Section: Tinbergen Question 3: How Does the Trait Develop In An Inmentioning
confidence: 99%
“…This agrees with developmental plasticity demonstrated in other fishes such as the black bream (Shand et al 2008). The only study to examine adult plasticity showed that adult tilapia were not plastic to altered lighting environments (Hornsby et al 2013). This lack of adult plasticity is similar to studies of the South American species Aequidens pulcher, which found no shifts in photoreceptor sensitivities when fish were reared under different colored lights in the lab (Wagner and Kroger 2005).…”
Section: Tinbergen Question 3: How Does the Trait Develop In An Inmentioning
confidence: 99%
“…The light environment is a factor known to drive both the reception and production of visual signals of fishes (Hornsby et al 2013;Hurtado-Gonzales et al 2014;Shin and Choi 2014;Terai et al 2006;Tezuka et al 2014). Indeed, the present study showed that the spectral sensitivities of P. h. himantegus and P. h. chii are distinct: P. h. himantegus is more sensitive than P. h. chii to longer wavelength light, while it is less sensitive than P. h. chii at shorter wavelengths.…”
Section: Discussionmentioning
confidence: 47%
“…The photosensitivity peaks present in the UV (380 nm) and middlewavelength (480 nm) regions were close to the maximum absorbances (λ max ) of the tilapia retinal cone photopigments (SWS1, 360 nm; RH2b, 472 nm) (Spady et al, 2006). To better understand the interaction between photopigments, the visual pigment templates of SWS1 and RH2b were fitted to the erythrophore action spectrum plot (Govardovskii et al, 2000;Sabbah et al, 2012;Hornsby et al, 2013). Because of the opposing effects elicited by these two photopigments, a neutral area of the antagonistic interaction is suggested to be located in the spectral region near 440-460 nm, which is within the overlapping area of the α-bands (the primary absorption peaks) of these two photopigments.…”
Section: Action Spectrum Of Erythrophoresmentioning
confidence: 99%
“…The spectral characteristics of each pigment have been well-established from absorbance spectra of in vitro reconstituted proteins and from in situ microspectrophotometry (MSP) measurement (Spady et al, 2006;Carleton et al, 2008;Lisney et al, 2010). Based on reported sensitivity peaks of tilapia cone pigments (Spady et al, 2006), absorption templates were used to fit the photosensitivity curve using a least-squares fit as described previously (Govardovskii et al, 2000;Anderson et al, 2010;Hornsby et al, 2013). In the action spectrum curve of tilapia erythrophores, two peaks present at 380 and 480 nm were close to the maximum absorbances (λ max ) of the retinal cone photopigments (SWS1, 360 nm; RH2b, 472 nm; with 11-cisretinal; Spady et al, 2006).…”
Section: Curve Fittingmentioning
confidence: 99%
See 1 more Smart Citation